Cultivo de Tectona grandis L.f. no Estado do Espírito Santo - Guimarães, Mariana Abdalla Prata (2012)
The objective was to create a map of zoning edaphoclimatic for teak in Espírito Santo, characterize six teak stands in southern Espírito Santo, and evaluate the genetic variability in progenies of Tectona grandis Lf in the municipality of Alegre, state of Espírito Santo. The work was divided into three chapters. At first, we used the fuzzy logic, in the desktop ArcGIS 9.2/ArcMap®, from time series of accumulated rainfall annual average, air temperature, water deficit accumulated annual and texture of soils. From the IDW and Reclass tool were generated maps of each factor, considering the indexes for teak. By overlaying these maps, we obtained the map of zoning edaphoclimatic. The southern and south central coastal showed aptitude for the cultivation of the species. The western region was classified as suitable restriction, because of the had rocky outcrops, but were masked by the methodology. The mountainous and north regions were classified as able-restricted, due to water factors. In the second chapter, we evaluated six teak stands in the municipalities of Cachoeiro de Itapemirim, Muqui and Mimoso do Sul. The stands were divided in plots of 9,0 m x 12,0 m, and evaluated 6 plots in each stand, randomly selected, noting the variables: total height, merchantable height, circumference, attack of pests and diseases and the presence of thick branches and twisting on the shaft. The stands of the region are small, and showed low values to characteristics evaluated, despite being located in areas suitable for the cultivation of the species. In the third chapter, it was used as treatment 50 progenies of half-brothers teak, established in a randomized block design, spaced 3,0 m x 2,0 m. The monitoring was conducted at 6 and 12 months after planting, where it was evaluated: i) the diameter of the stem base, ii) total height and iii) survival. The variables were analyzed using the methodology of mixed linear model univariate and multivariate, through of the SELEGEN-REML/BLUP and Genes programs. There was low correlation and low genetic variability for all characters at 6 and 12 months, which can be attributed to genetic basis restricted, to the soil used in the experiment or the age of the plants. The progenies 15, 20, 21 and 41 were higher in Medium-Rank for all traits